Religious Actors and Discourses in Social Protest - Pérez, Rolando (2015)
This article analyses the roles played by the actors related to religious groups,the way that they rebuild their participation and representation in the publicspace from their involvement in the initiative of social protest about the reclaimand defense of certain civil rights. In this regard, the article addresses the relationship between religion and politics, and furthermore specifically, the way inwhich religious human capital contributes to the process of collective actionsand social mobilization. At the same time, it offers some ideas regarding theway in which religious speech and public practice is shaped by cultural mediatization.